Sadd al-Dharī'ah, Social Media, and Korean Muslim Converts: A Legal Theory Analysis of Digital Content Creation - Kim Fatima Soo-Jung; Cong Abdullah Sung-min; Vermeersch Hae-young; Muhd Zahiri bin Haji Awang Mat (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2025)
This article examines the application of the Islamic legal principle of Sadd al-Dharī'ah (blocking the means to harm) in the context of digital content creation by Korean Muslim converts on social media. The study investigates how the principle, traditionally employed to prevent potential harm, is interpreted and applied to the ethical challenges of producing and sharing Islamic content in digital spaces. Employing qualitative methods, the research draws on interviews with Korean Muslim content creators, analysis of their digital materials, and a review of classical and contemporary Islamic legal texts. The findings reveal a complex negotiation between promoting Islamic teachings and addressing potential risks, such as the misinterpretation of content, commodification of religious messages, and online harassment. Content creators navigate these challenges by balancing the principle of Sadd al-Dharī'ah with the goals of da‘wah (Islamic outreach) and the demands of social media algorithms, often prioritizing harm prevention while striving for engagement and authenticity. This study highlights the dynamic application of Islamic legal theory in the rapidly evolving digital landscape, offering insights into how Korean Muslims convert and contextualize their religious obligations within modern technological frameworks. By addressing the interplay between ethical content creation and religious principles, the research contributes to broader discussions on the relevance of classical Islamic jurisprudence in addressing contemporary issues. It underscores the need for further scholarly engagement with digital ethics in Islamic legal thought and provides practical recommendations for Muslim content creators navigating similar challenges worldwide.